The Impact of Contractual Savings Institutions on Securities Markets - Impavido, Gregorio; Musalem, Alberto R.; Tressel, Thierry (World Bank, Washington, DC, 2014)
The authors assess empirically the impact of contractual savings institutions portfolios (pension funds and life insurance companies) on securities markets, for example, depth and liquidity in the domestic stock market, and depth in the domestic bond market. They discuss how the institutionalization of savings can modify financial markets through the lengthening of securities' maturities. The results are the following: 1) An increase in assets of contractual savings institutions relative to domestic financial assets has a positive impact on the depth of stock and bond markets on average. 2) The impact on stock market depth and liquidity is nonlinear: it is stronger in countries where corporate information is more transparent. 3) There is evidence of a significant heterogeneity among countries: contractual savings have a stronger impact on securities markets in countries where the financial system is market based, pension fund contributions are mandatory, and international transactions in securities are lower. 4) The authors do not find that the impact of contractual savings institutions on securities markets is explained by the overall level of development, education, demographic structure or the legal environment.